PENGARUH BEBAN KERJA DAN KONFLIK PERAN TERHADAP KINERJA KARYAWAN PT. PRIMATAMA MULIA JAYA (PMJ) KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Endarwita Endarwita; Mai Yuliza; Puspa Resita (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine the effect of workload and role conflict on employee performance of PT. Primatama Mulia Jaya (PMJ). The number of samples in this study were 72 people. Based on the results of the study, there is a significant influence between workload on employee performance, as evidenced by the value of T-statistic of 5,804 with a significant value of 0.000 > 0.05. Role conflict has a significant effect on employee performance, the value of T-statistic is 3.135 and a significant value is 0.000 < 0.05. If seen simultaneously there is a significant effect of workload on employee performance, and role conflict has a significant effect on employee performance, as evidenced by the F value of 23,315 with a significant level of 0.000